The Vibrational Spectroscopy of the Valence Bonds of Cu-Doped TiO2 Using Electronegativity Principle Quantitative Calculations - Ji-Kang Yan; Jun-Yu Chen; Guo-You Gan (Journal of Spectroscopy)
The purpose of this study is to investigate the influence of Cu on TiO2 phase transformation and regioselectivity. TiO2 samples doped with different amounts of Cu2+ ions were synthesized by the sol-gel method. The phase and vibrational mode were characterized by X-ray diffraction (XRD), Fourier infrared spectroscopy (FTIR), and transmission electron microscope (TEM). The XRD phase analysis shows that the lattice parameters have not changed after Cu incorporation. In addition, the content of rutile increased obviously after Cu doping. This indicated that the addition of Cu obviously promoted the transformation from anatase phase to rutile phase. The vibration frequencies were calculated based on the principle of electronegativity. All types of bonds were qualitatively and quantitatively analyzed. The content of TiA-O, TiR-O, and H-O in the undoped TiO2 samples is 23.87%, 16.30%, and 7.41%, respectively. In the same way, the content of TiA-O, TiR-O, H-O, CuAi-O, and CuRi-O in the 2.5 mol%Cu-doped TiO2 samples is 21.23%, 18.56%, 7.34%, and 0.98%, respectively. For the 5 mol%Cu-doped TiO2 samples, the content of TiA-O, TiR-O, H-O, CuAi-O, CuRi-O, CuAs-O, and CuRs-O is 18.75%, 20.11%, 7.47%, 2.56%, 3.9%, 1.55%, and 2.35%, respectively. Cu was not present at substitutional sites in the 2.5 mol% doped sample, but Cu was present in the 2.5 mol% doped sample. It is indicated that Cu was more likely to exist in the form of interstitial position in the TiO2 lattice, with the number of Cu atoms in the interstitial position reaching saturation, and this forced Cu to replace Ti. The TEM shows that the stripes of different periods and orientations overlapped each other to form the Moiré patterns. In addition, the diffraction patterns of the Moiré image were slightly different from that of the matrix. The Cu replaced Ti position and the Cu atoms mixed into interstitial sites in the TiO2 lattice. The theoretical calculation was consistent with the experimental results.